Analysis of Employees’ Performance in Department of Health Palu City, Central Sulawesi Province - Putri Ayu Wandira; Munir Salham; Mohamad Andri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Performance is the work result in both quality and quantity that can be achieved by an employee in carrying out his main duties and functions as an employee by responsibilities assigned or given to him. The purpose of this research is to determine and analyze the performance of employees at the health department of Palu city. The type of research is qualitative and the data collection techniques are observation, interview, and documentation. The informants taken in this study are 1 (one) as Head of Subdivision of Personnel, 1 Head of Subdivision of Health Services and Resources, 1 civil servant, and 1 noncivil servant. The results show the performance of Health Office employees in terms of quantity had many work programs carried out according to the planned targets, regarding the punctuality of employees who are serious enough in doing their work and trying to finish on time because each employee already has a job description, and in terms of independence, employees have taken the initiative incomplete their work without being supervised by the leadership, although there are still some obstacles faced in achieving the organization’s work goals. This research suggests that the Health Agencies further improve massive strategies in developing and improving employee performance.